2018
DOI: 10.1002/jbio.201700308
|View full text |Cite
|
Sign up to set email alerts
|

Real‐time monitoring prefrontal activities during online video game playing by functional near‐infrared spectroscopy

Abstract: A growing body of literature has suggested that video game playing can induce functional and structural plasticity of the brain. The underlying mechanisms, however, remain poorly understood. In this study, functional near-infrared spectroscopy (fNIRS) was used to record prefrontal activities in 24 experienced game players when they played a massively multiplayer online battle arena video game, League of Legends (LOL), under naturalistic conditions. It was observed that game onset was associated with significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 90 publications
1
14
0
Order By: Relevance
“…The mechanisms underlying changes following video game interventions remain unclear, although they might be related to tonic/phasic activation or inhibition of affected brain regions during video game playing [ 73 ] that make the participants feel satisfied. Specifically, psychological satisfaction and pleasure might be related to the various feedback mechanisms provided to the player by the active video game.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms underlying changes following video game interventions remain unclear, although they might be related to tonic/phasic activation or inhibition of affected brain regions during video game playing [ 73 ] that make the participants feel satisfied. Specifically, psychological satisfaction and pleasure might be related to the various feedback mechanisms provided to the player by the active video game.…”
Section: Discussionmentioning
confidence: 99%
“…An event-related approach ( Cavanagh & Castellanos, 2016 ; Li et al, 2018 ) was used to analyze the HbO and HbR concentrations accompanying specific game events. Video recordings of participants’ gameplay was analyzed by an experienced LOL player to mark the time point of the occurrence of positive or negative events.…”
Section: Methodsmentioning
confidence: 99%
“…A previous study using fNIRS while participants played LOL reported similar numbers of events (average of 2.5–4.58 events) and ranges (e.g., 0–8. 1–14) per condition and reported the numbers are sufficient for analysis ( Li et al, 2018 ). It is noteworthy that the wide range in the number of events tagged to each individual in both our study and the aforementioned study is due to the variability of each game session.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In different stages of a game, latency -the time taken to trigger a strong emotional response -can also differ. In particular, the onset of a game has been found to rapidly trigger activity in the prefrontal cortex (the area of the brain that involves executive functioning) (Li et al, 2018). Recognising these characteristics, and recalling the manner in which the girls' L2 communication rapidly transitions from a state of hesitancy (line 2) and experienced coercion (line 4), to a state of intense activity (lines 26-29), these interactions appear to be better explained in terms of an experience specific to being immersed in a digital game.…”
Section: Willingness To Communicate?mentioning
confidence: 99%